Transitioning towards a sustainable food city. Issue 7 (4th November 2019) - Quest, Jill; Shiel, Chris; Watson, Sarah
Abstract : Purpose: This paper aims to provide a case study of a capacity building project and critical reflection in relation to transitioning to a sustainable food city. Design/methodology/approach: A case study research approach was adopted involving two research initiatives: first, a survey to elicit stakeholders' understanding of sustainable local food, with a view to creating a shared agenda and informing future strategic direction and second a combination of research approaches, including paired discussions, generation of pictorial outputs and a workshop, aimed to inform the future vision and mission of the Partnership. Findings: Collaboration with stakeholders through a variety of research initiatives has facilitated the development of a sustainable food city partnership, with the overarching aim of achieving a transition towards a more sustainable food system. Moreover, collaboration has contributed to the transition of the Partnership to ensure sustainability and continuity after the initial funding stage. Research limitations/implications: While universities have an important role to play in guiding direction and shaping new community initiatives for sustainability in their regions, the challenges, resources and time involved may be under-estimated; these projects take considerable time to yield fruit. Practical implications: The findings of the study will be of interest to those working in the community to promote education for sustainable development and better food systems. Originality/value: This paper addresses a gap in the literature in relation to universities and their collaboration with key stakeholders in building capacity and contributing to local sustainability transitions.